WAYFINDING SEBAGAI MEDIA PROMOSI TERPADU PADA MUSEUM NEGERI SUMATERA SELATAN - Ferry Muhammad Rahman Ferry; Yosef Yulius; Aji Windu Viatra (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract : The South Sumatra State Museum consists of 5 museums, namely Balaputra Dewa Museum, Sultan Mahmud Badaruddin II Museum, Textile Museum, and Sriwijaya Museum. However, these 5 museums do not have any identity at all. Therefore, the author wants to provide an educational information media that can inform and invite museum managers to pay more attention to how to manage museums in this modern convergence era. It is expected that the purpose of this design is intended as a medium of education and information that can provide knowledge to museum managers to increase the number of local and foreign tourist visits.